Displacement, Belonging, and Land Rights in Grand Gedeh, Liberia: Almost at Home Abroad?. (29th November 2017) - Bjørkhaug, Ingunn; Bøås, Morten; Kebede, Tewodros
Abstract: Conflicts over local land rights between groups considered as "sons of the soil" and newcomers such as refugees can trigger autochthony-inspired violence. However, such conflicts are not always manifested, even when the conditions are in place. The question we explore in this article is whether such conflicts are less likely to emerge if the "other" is from a group with a longstanding bond of interethnic allegiance with the host community. Based on ethnographic data from host–refugee communities in Grand Gedeh, Liberia, we revisit previous attempts to explain economic and social relations between majority and minority groups. Our main finding is that in this part of Africa no prior special status will fundamentally alter the established ways of incorporating strangers into the community. Résumé: Les conflits sur les droits fonciers locaux entre les groupes considérés comme "fils du sol" et les nouveaux arrivants, tels que les réfugiés, peuvent déclencher une violence inspirée par l'autochtonie. Cependant, de tels conflits ne se manifestent pas toujours, même lorsque les conditions de conflit sont en place. Cet article explore la question de savoir si ces conflits sont moins susceptibles d'émerger si l' "autre" provient d'un groupe ayant un lien de longue date d'allégeance interethnique. Sur les bases de données ethnographiques des communautés hôtes–réfugiés à Grand Gedeh, Libéria, il revisite les tentatives précédentes d'explication des relations économiques et sociales entre les groupes majoritaires et minoritaires. La conclusion principale est qu'aucun statut spécial antérieur ne modifie fondamentalement les moyens établis d'intégrer des étrangers dans cette partie de l'Afrique.